Microleakage of Class-V Composite Restorations with Different Bonding Systems on Fluorosed Teeth - Küçükeşmen, Çiḡdem (Dental Investigations Society, 2008)
OBJECTIVES: To examine the effects of dental fluorosis and total and self-etch bonding systems on microleakage of Class-V composite restorations in permanent molar teeth. METHODS: Teeth were classified as three main groups according to Thylstrup-Fejerskov Index (TFI) as TFI=0, TFI=1–3 and TFI=4. Total and self-etching/bonding procedures were determined for each main group. Total-etching procedures were acid-etching for 30s and acid-etching for 60s with Single Bond/total-etch bonding system. Self-etching procedure was applied with Prompt-L-Pop/self-etch bonding system. 63 box-shaped Class-V cavities (4 × 2 × 2 mm) were prepared on mid-buccal/palatinal/lingual surfaces of teeth for totalling nine test groups (n=7). Restorations with composite material (Charisma) polymerized with halogen unit for 40s. Teeth were thermocycled between +5°C – +55°C (×500), immersed in 0.5% basic-fuchsin solution (37°C, 24h) and separated longitudinally in bucco-lingual direction. Dye penetration was examined under stereomicroscope (3.2 × 10). RESULTS: Microleakage levels were higher in teeth of TFI=4 than TFI=0 occlusally or cervically (P<.05). In TFI=0; total-etched teeth for 30s have statistically shown more leakage than total-etched teeth for 60s occlusally or cervically (P<.05). In TFI=4; microleakage levels were significantly higher for 30s than 60s cervically (P<.05). For all TFI levels, microleakage was commonly increased with self-etch system than total-etch system (P<.05). Generally, higher leakage was present at cervical margins than occlusal margins (P<.05). CONCLUSIONS: Microleakage has increased by severity of dental fluorosis. Generally, more leakage was observed in total-etched teeth for 30s than 60s. Microleakage was commonly higher in self-etched teeth than total-etched teeth. More leakage was present at cervical margins than occlusal margins.